Analisis Kematangan Layanan Teknologi Informasi Hotel Menggunakan ITIL V.3 Framework - Istiana Ruswita; Dedy Syamsuar (LPPM UBHINUS MALANG, 2023)
The standardization of IT implementation in modern companies, including hotels is the impact of the deployment of IT sustainability. This study aims to analyze the maturity level of IT service management or ITSM at Hotel Santika Premiere Palembang using the Information Technology Infrastructure Library (ITIL) V.3 framework. The population in this study were all employees and the samples are 29 respondents obtained from RACI mapping. Gap analysis is used to determine the value of the gap between actual conditions and ideal conditions in 28 sub domains of the ITIL V3 process. Based on the overall analysis and assessment process, the maturity level of IT service management is 2.79. Overall IT service management maturity level is at level 3 (defined), i.e. each process in the ITIL V.3 sub domain has been defined but in its application there are still many shortcomings such as lack of documentation and reporting, no clear measurement of the quality of IT service management, and no IT service strategies that are aligned with the company's business objectives. Recommendations are compiled based on the subdomain with the highest gap value so that improvements can be made immediately to reduce the gap and meet the expected condition.